2018
DOI: 10.1007/s10705-018-9958-y
|View full text |Cite
|
Sign up to set email alerts
|

Fertilizer response and nitrogen use efficiency in African smallholder maize farms

Abstract: Improving fertilizer recommendations for farmers is essential to increase food security in smallholder landscapes. Currently, blanket recommendations are provided across agro-ecological zones, although fertilizer response and nutrient use efficiency by maize crop are spatially variable. We aimed to identify factors that could help to refine fertilizer recommendation by analyzing the variability in fertilizer response (FR) and the agronomic nitrogen use efficiency (N-AE). A literature search for on-farm studies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
38
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 77 publications
(49 citation statements)
references
References 57 publications
6
38
1
Order By: Relevance
“…Our findings show that N fertilizer management is differentially influenced by agro‐ecology. This implies that instead of promoting blanket fertilizer use in African smallholder farms (Ichami, Shepherd, Sila, Stoorvogel, & Hoffland, 2019), fertilizer recommendations should consider the climatic and geospatial variations which potentially influence crop response to fertilizer.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings show that N fertilizer management is differentially influenced by agro‐ecology. This implies that instead of promoting blanket fertilizer use in African smallholder farms (Ichami, Shepherd, Sila, Stoorvogel, & Hoffland, 2019), fertilizer recommendations should consider the climatic and geospatial variations which potentially influence crop response to fertilizer.…”
Section: Discussionmentioning
confidence: 99%
“…SOC ranged from 1.0 to 2.2%, which is similar to previously reported values found across Tanzania (Bhargava, Vagen, & Gassner, ) and is on the low end of SOC content needed for effective fertilizer use based on the literature. Some studies have found fertilizer response from soils as low as 1–1.5% SOC, while other studies suggest a higher threshold of 2.7% SOC is needed for effective fertilizer use (Ichami, Shepherd, Sila, Stoorvogel, & Hoffland, ; Kihara et al, ; Marenya & Barrett, ). Soil nitrogen was similarly low across regions, with a range of 0.03–0.07%, well below the 0.2% threshold used in Berazneva et al (), which also measured soil fertility of agricultural land in Tanzania.…”
Section: Discussionmentioning
confidence: 99%
“…A key assumption here is that nutrient contents are reasonably constant, and yield variation in unfertilized plots is determined by variation in soil nutrient supply. Yields in unfertilized control treatment plots have previously been used to interpret Ronner et al, 2016;, and explain crop yield response patterns to fertilizer applications on smallholder farms of SSA (Ichami et al, 2019). Theoretical relationships between for example, crop yield with fertilizer N applications and yield in unfertilized control treatment plots have also been developed (Vanlauwe et al, 2011), underscoring the utility of crop yields in unfertilized plots as an indicator of soil nutrient supply.…”
Section: Discussionmentioning
confidence: 99%
“…Given the limited ability of soil analysis to predict expected yield response patterns described above, more easily accessible indicators of potential soil supply may provide a more cost-effective way of improving yield response predictions. Observed strong relationships between yield in control plots without fertilization and soil fertility (Vanlauwe et al, 2006) and maize yield response to fertilizer applications (Ichami et al, 2019) suggests that control-plot yield is indicative of potential soil nutrient supply. Given common practices of minimal or no fertilizer application in smallholder farms of SSA, actual farmer yields under current practices may be a better and more costeffective predictor of potential soil nutrient supply when compared to soil analysis.…”
Section: Introductionmentioning
confidence: 99%